2022
DOI: 10.1111/eci.13738
|View full text |Cite
|
Sign up to set email alerts
|

Poor self‐reported sleep is associated with risk factors for cardiovascular disease: A cross‐sectional analysis in half a million adults

Abstract: Background Sleep is known to affect cardiovascular health, but some controversy exists on the independent association between different sleep characteristics (duration, restfulness, difficulties falling asleep) and specific risk factors for cardiovascular disease (CVD). We aimed to assess the association between self‐reported sleep characteristics and the likelihood of major CVD risk factors. Methods Totally, 521,364 Spanish workers (32% female, 44 ± 9 years [18–64]) insured by an occupational risk prevention … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
2
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
5
1
1

Relationship

0
7

Authors

Journals

citations
Cited by 11 publications
(2 citation statements)
references
References 55 publications
0
2
0
Order By: Relevance
“…I read with great interest the study of Valenzuela et al 1 regarding the association between self-reported sleep characteristics and cardiovascular disease (CVD) risk factors. Poor sleep was defined by the existence of excessively short (<6 h/d) or long (>9 h/d) sleep, unrestful sleep or difficulties to fall asleep.…”
Section: Self-reported Sleep Characteristics and Cardiovascular Disea...mentioning
confidence: 99%
“…I read with great interest the study of Valenzuela et al 1 regarding the association between self-reported sleep characteristics and cardiovascular disease (CVD) risk factors. Poor sleep was defined by the existence of excessively short (<6 h/d) or long (>9 h/d) sleep, unrestful sleep or difficulties to fall asleep.…”
Section: Self-reported Sleep Characteristics and Cardiovascular Disea...mentioning
confidence: 99%
“…With humans spending approximately one-third of their lives sleeping, sleep's implications influence the entire spectrum of health and disease. The scientific community has increasingly recognized the bidirectional relationship between sleep and cardiovascular function, with changes in sleep macroarchitecture being both a consequence and a contributor to cardiovascular diseases [1][2][3][4] .…”
Section: Introductionmentioning
confidence: 99%